Educational needs in cultural and arts entrepreneurship of women from marginalised backgrounds : A needs analysis for a social design intervention - Souleles, Nicos; Savva, Stefania; Ferreira, Ana Margarida; Laghos, Andrew (My University, 2020)
Despite the recognition that cultural and creative industries can foster significant economic potential and are one of Europe's most dynamic sectors, contributing to the creation of millions of jobs across the European Union, there is a noticeable lack of cultural and arts entrepreneurship programmes of study. The project CREATION (Cultural and Arts Entrepreneurship in Adult Education), funded under Erasmus+ Strategic Partnerships for adult education, seeks to redress this situation through a social design intervention comprising the development of a framework for adult education for the creative and cultural sectors across Europe, with a specific focus on aspiring women entrepreneurs from marginalised backgrounds (migrants, refugees and asylum seekers). This study provides a needs analysis to inform the identification of the required educational needs for the target groups. It comprises desk research of the related literature plus data from an online survey. The synthesis of the prominent themes that emerged from this study indicates the need for a multifaceted instructional design approach that combines both the essential generic skills in entrepreneurship and acknowledges the structural, contextual and educational challenges that are characteristic of the target groups.
Keywords: Culture; Arts; Education; Entrepreneurship; Women; Marginalised